PO146 Defining the domains of a composite assessment tool for ms. (1st December 2017) - Young, Carolyn; Chandran, Siddharthan; Molyneux, Paul; Overell, James; Palace, Jacqueline; Pettit, Laura J; Resemann, Henrike K; Robertson, Neil; Williams, Alison
Abstract : Introduction: Disease assessment measures in multiple sclerosis (MS) are often underused, reporting of assessments varies between centres, and there is no standardised patient-reported measure used across the UK. Objective: To define the components of a novel, patient-reported, composite assessment tool for MS to improve the consistency of MS management. Methods: A steering committee (n=6) was convened to postulate potential domains, following which consensus was sought from 22 UK-based neurologists in a modified three-round Delphi process (≥70% agreement required for domain inclusion). New domains could arise from the group. Results: In round one, the Delphi panel reached consensus (n=16/18, 88.9%) that a patient-reported, composite profile measure would add value to UK clinical practice. Following three rounds of the Delphi process, panellists reached consensus agreement to include 9/11 of the proposed domains: fatigue, upper-limb function, mobility, cognition, vision, pain, bladder function, bowel function and quality of life. Two domains did not achieve consensus for inclusion by Delphi round three: depression (n=13/19, 68.4%) and sexual function (n=11/19, 57.9%). Conclusion: Nine domains reached the predetermined threshold for inclusion, demonstrating consensus of opinion for the components of a patient-reported, composite assessment tool for MS and the value of such a measure in UK clinical practice.